Tunable emission of AgIn5S8 and ZnAgIn5S8 nanocrystals: electrosynthesis, characterization and optical application. (June 2020) - Sousa, F.L.N.; Freitas, D.V.; Silva, R.R.; Silva, S.E.; Jesus, A.C.; Mansur, H.S.; Azevedo, W.M.; Navarro, M.
Abstract: Ternary AgIn5 S8 (AIS) and quaternary ZnAgIn5 S8 -alloy (ZAIS) nanocrystals, stabilized by L-glutathione, were produced by a clean and eco-friendly electrochemical method, eliminating the need of reducing agents. AIS-GSH colloidal solution was obtained by constant current electrolysis (i = 30 mA) in cavity cell. S 2− ions (0.051 mmol) were generated into a graphite powder macroelectrode, reacting in the intermediate compartment of the cell containing Ag + /In 3+ aqueous solution at different ratios (0.5, 0.28, 0.18, and 0.14), and 0.025 mmol/L −1 glutathione (GSH). ZAIS-GSH NCs were synthesized in the same cavity cell containing the previously prepared AIS-GSH solution. A paired electrolysis (i = 30 mA) was used for simultaneous production of Zn 2+ and S 2− (Zn 0 sacrificial anode and graphite powder macroelectrode/S 0 cathode). The electrochemical method promoted a high reproducibility and efficient luminescence in the preparations of NCs. The sizes of the AIS-GSH and ZAIS-GSH nanoparticles were determined by HRTM (3.4 and 4.0 nm, respectively), and quantum yields reaching 16% (AIS-GSH, Ag + /In 3+ = 0.18). The spectrophotometric characterization showed that Ag + /In 3+ ratio can be used for the tuning of the AIS-GSH nanoparticle emission wavelength, which is associated to electronic defects introduced in the NCs lattice. XRD/EDS analysis of ZAIS-GSH nanoparticles point out to Zn 2+ ion-exchange into the AIS-GSH lattice. XPS analysis was carried out at different etching levels of the ZAIS nanocrystals surface, making possible to identify the 2p Zn doublet signal, indicating two different Zn 2+ sites in the alloy structure. Time-resolved spectroscopy measurements/decay curves were carried out to evaluate the effect of silver amount on radioactive and non-radioactive terms. Additionally, the AIS-GSH and ZAIS-GSH photoluminescence and stability were used to produce the active parts of commercial white LEDs, and modulate the colour perception from the respective emission bands. Graphical abstract: Image 1 Highlights: AgIn5 S8 nanocrystals (NCs) were synthesized by eco-friendly electrochemical method. The full electrochemical procedure lead to alloy between ZnS–AgIn5 S8 . The role of Ag and Zn in the NCs PL was investigated by time resolved spectroscopy. The regime to inserption of Zn 2+ to AgIn5 S8 NCs. Modulation of LED emission colour with QD film deposition.